Diarylamine-Guided Carboxamide Derivatives: Synthesis, Biological Evaluation, and Potential Mechanism of Action - Ke, Shaoyong; Huang, Wenbo; Zhang, Zhigang; Wang, Yueying; Zhang, Yani; Wu, Zhaoyuan; Fang, Wei; Wan, Zhongyi; Gong, Yan; Yang, Jingzhong; Wang, Kaimei; Shi, Liqiao (Frontiers in Chemistry, 2022)
Diarylamines are a class of important skeleton widely existing in drugs or natural products. To discover novel diarylamine analogues as potential drugs, two series of diamide and carboxamide derivatives containing diarylamine scaffold were designed, synthesized and evaluated for their potential cytotoxic activities. The bioassay results indicated that some of the obtained compounds (C5, C6, C7, C11) exhibited good cytotoxic effect on cancer cell lines (SGC-7901, A875, HepG2), especially, compound C11 present significantly selective proliferation inhibition activity on cancer and normal cell lines (MARC145). In addition, the possible apoptosis induction for highly potential molecules was investigated, which present compound C11 could be used as novel lead compound for discovery of promising anticancer agents.